Waste-derived CaO Modified TiO₂ with Reduced Band Gap and Improved Photoresponse under Visible Light - Siti Rodiah; Ratih Rizqi Nirwana; Desti Erviana; Nina Ariesta; Damayanti Iskandar; Hapin Afriyani (Pandawa Institute, 2026)
Titanium dioxide (TiO₂) is the most extensively investigated photocatalysts, but its high band gap energy limits its photoactivity primarily to the ultraviolet region. This study presents a green approach to enhanced visible-light absorption of TiO₂ by utilizing calcined golden snail shells as a sustainable and low-cost precursor for CaO dopant. The TiO₂-CaO composites were synthesized via a simple loading technique. Characterization confirmed the successful distribution of CaO onto the TiO₂ surface, reducing in the band gap energy of TiO₂ from 3.334 eV to 3.322 eV. This modification substantially broadened the material’s light absorption into the visible spectrum. The optimized composites demonstrated feasible photocatalytic activity for the reduction of CO₂ under simulated solar irradiation with the addition of Clitoria ternatea photosensitizer, achieving initial activity higher than that of pure TiO₂. This work successfully combines the waste-derived CaO, offering a promising, environmentally friendly, and highly effective green material to improved photoresponse under visible light of TiO₂.